2019
DOI: 10.1021/acsbiomaterials.8b01372
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Osteoblast Differentiation of Adipose-Derived Mesenchymal Stem Cells Using a Cobalt-Doped CaP/Silk Fibroin Scaffold

Abstract: A major problem in the treatment of large bone defects is the inability to provide an adequate blood supply to the implantation site. Therefore, a bone regeneration strategy that provides an adequate supply of vessels would address this need. Cobalt (Co2+), because of its ability to induce hypoxia, has been used to accelerate new vessel formation. In this study, we used a freeze-drying technique to fabricate a scaffold that consisted of Co2+-doped calcium phosphate (CaP) [e.g., hydroxyapatite (HA)] and natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Adult male Wistar rats (weighing 250–300 g) were obtained from the Pasteur Institute (Tehran, Iran) and kept under standard conditions. The Ethics Committee of Tehran University of Medical Sciences approved all the animal experiments (ethical code: IR.TUMS.REC.1394.1594) (Fani et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult male Wistar rats (weighing 250–300 g) were obtained from the Pasteur Institute (Tehran, Iran) and kept under standard conditions. The Ethics Committee of Tehran University of Medical Sciences approved all the animal experiments (ethical code: IR.TUMS.REC.1394.1594) (Fani et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of ADSCs was carried out according to ethical instruction of Tehran University of Medical Sciences, Tehran, Iran using previously described protocols (Fani et al, ). In brief, the abdominal adipose tissue was obtained from the healthy Wistar rat.…”
Section: Methodsmentioning
confidence: 99%
“…Cobalt (Co 2+ ) has also been used as a dopant with silk owing to its unique ability to stimulate neovascularization. Co 2+ when used with HA/SF scaffold, makes a great candidate for inducing angiogenesis and bone formation in vitro and in vivo ( Fani et al, 2019 ). Therefore, inorganic elements can also be utilized in silk scaffolds to guide cellular differentiation.…”
Section: Tailoring Silk Biomaterials To Control Cellular Fatementioning
confidence: 99%
“…The treatment of large bone defects due to trauma, infections, tumors, or genetic malformations, represents a major challenge for clinicians 28 . Promoting bone tissue regeneration through enhanced osteogenesis and angiogenesis is a desirable property of some biomaterials for bone repair 29 . In the previous study, we showed that immobilized CMC/LAP on PCL nanofibers could significantly support the proliferation and differentiation of stem cells to osteoblasts without using any external osteoinductive agent 18 .…”
Section: Resultsmentioning
confidence: 99%